Analisis Business Model Canvas pada Perusahaan Ready Mix Concrete PT XYZ - Risti, Ramadinda; Lukman, Syukri; Adrianto, Fajri (SAFE-Network, 2023)
The purpose of this study is to analyze the business model canvas (BMC) at ready mix concrete company PT. XYZ. This study used purposive sampling, the informants in this study were directors and heads of divisions. Data collection was carried out by observation, interviews, Forum Group Discussion (FGD) and literature studies. The research phase begins with the Business Model Canvas and SWOT, problem identification, data collection, data analysis, interpretation of results and conclusions. Through the analysis described above, the result is that PT. XYZ has implemented a Business Model Canvas. Results of the SWOT matrix by writing down opportunities and threats on the vertical side and strengths and weaknesses on the horizontal side. Based on the results of the SWOT matrix, there are 13 alternative strategies that PT XYZ can choose from. After conducting a Swot analysis of the business model canvas, then a new business model canvas is formed for the company's business model. The limitations of this study are limited to only using the Business Model Canvas analysis method and SWOT analysis, it is recommended to use the analytical method using QSPM to get better results. The informants in this study only focused on informants who came from internal company PT. XYZ. Suggested further research by adding informants from external parties PT. XYZ company.